2013
DOI: 10.1080/10810730.2012.743624
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Mediation Model: Factors Influencing Public Knowledge of the H1N1 Pandemic and Intention to Take Precautionary Behaviors

Abstract: This study uses the cognitive mediation model as the theoretical framework to examine the influence of motivations, communication, and news elaboration on public knowledge of the H1N1 pandemic and the intention to take precautionary behaviors in Singapore. Using a nationally representative random digit dialing telephone survey of 1,055 adult Singaporeans, the authors' results show that the cognitive mediation model can be applied to health contexts, in which motivations (surveillance gratification, guidance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(134 citation statements)
references
References 80 publications
6
119
3
Order By: Relevance
“…As women engaged in conversations, they would learn new associations between breast cancer and health concepts. Even though the nonsignificant relationship with factual knowledge runs counter to past findings (e.g., Ho et al, 2013), it suggests that women may turn to interpersonal networks more for social support than for content. Elaboration was positively associated with both knowledge dimensions Eveland & Thomson, 2006;.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…As women engaged in conversations, they would learn new associations between breast cancer and health concepts. Even though the nonsignificant relationship with factual knowledge runs counter to past findings (e.g., Ho et al, 2013), it suggests that women may turn to interpersonal networks more for social support than for content. Elaboration was positively associated with both knowledge dimensions Eveland & Thomson, 2006;.…”
contrasting
confidence: 99%
“…The media makes salient certain issues, and as individuals pay attention to media content, the level of attention is associated with active cerebral processing of the information (Eveland, 2001;Ho et al, 2013). We postulate that attention to both online and offline media platforms will be associated with women's engagement in elaborative processing, as past studies have found support for these relationships (Eveland, Cortese, et al, 2004;Rimer & Glassman, 1999).…”
Section: Media Attention Interpersonal Communication and Elaborationmentioning
confidence: 75%
See 3 more Smart Citations